A escrita da história como crítica - Scott, Joan; Cardoso, Eduardo Wright; Damas, Naiara; Sanglard, Nathália (Revista de Teoria da História, 2023)
Tradução de: SCOTT, Joan W. History-writing as critique. In: JENKINS, Keith; MORGAN, Sue; MUNSLOW, Alun (Org.). Manifestos for History. London: Routledge, 2007. p. 19-38.